Benefits of teaching styles and student-centred methodologies in Physical Education - Jorge Agustín Zapatero Ayuso (Federación Extremeña de Balonmano; University of Extremadura, 2018)
The competence-based approach in education required a modification of the teaching performance, promoting the use of active and student-centred methodologies. The didactics of Physical Education has a previous theoretical framework that conceptualizes on the possibility of decision and participation of the student in the teaching process: the "Spectrum of Teaching Styles". This paper combines the perspective of the competency methodology and that of the "Spectrum Theory", with the aims of analysing the current situation of student-centred styles and methodologies in Physical Education at pre-university levels, and investigating the scientific evidence to could support the use of these methodologies in the classroom. A systematic review was conducted using the ISI Web of Science and Dialnet databases. The results suggest that teachers mostly use traditional or teacher-centred styles. Some benefits were found in the use of an active methodology as optimal levels of student motivation. It is necessary to advance in the knowledge of the possible benefits of these methodologies and the barriers to their development in the daily work of teachers.